A study on ecotourism package to West Malaysian tourist handled by Cat City Holidays / Melissa Supang Musa - Musa, Melissa Supang (Faculty of Business and Management, 2005)
Cat City Holidays Sdn. Bhd. (CCH) was incorporated on 25 May 1989 and was taken over on 14 June 1999) by a young and dynamic team with vast experience in the tourism industry. It is a tour operator licensed by the Ministry of Culture, Arts and Tourism Malaysia specializing in inbound and outbound tours, ticketing, and Meeting, Incentive, Conference and Exhibition (MICE) arrangements. Besides, van and coach rental services are also provided to customers. The vehicles are priced at competitive rates either self-driven or provided with a chauffeur driven service. The study was conducted on West Malaysian tourists that come in February. Thus the study will predominantly determine the West Malaysian tourists profile and their interest towards the ecotourism products in terms of culture, nature and adventure. A total of 70 sets of questionnaires were distributed to Cat City Holidays in the middle of February. Out of 70, only 52 respondents returned their questionnaires to the company. The finding was majority of the West Malaysian tourists came to Sarawak for holiday purpose. The tourists are interested to know the about diverse culture in Sarawak and also the historical sites and museum. Accommodation and facilities are the important elements in tourism industry. The tourists also agree that Sarawak has many places of interest and is an ideal place for ecotourism. It recommended that the tour guide should be well-trained. Review the inter-governmental agreement regarding the immigration department policy to ease the West Malaysian to enter Sarawak. The education programme in school should be implemented to promote and create awareness about the importance of the tourism industry to our state. Infrastructure needs significant investment and redevelopment and replacement to meet the demand and ability of the area to cater the tourists' needs. Theme park could be an added value to the ecotourism package.